A collaborative chain out of phase - Bård Paulsen; Tor Inge Romøren; Anders Grimsmo (International Journal of Integrated Care, 2013)
Introduction: The aim of this study is to explore the obstacles to collaborations between nurses in hospital and municipal care in the discharge of hospital patients who need continuing care. Methods: First, we conducted in-depth interviews of nurses in hospitals and nurses in municipal care. Second, we developed questionnaires and distributed them to a representative sample of Norwegian municipalities to study the representativeness of the most important findings from the interviews. Results: Municipal care nurses reported that the information they receive from hospital departments usually is insufficient for a complete understanding of a patient's needs. Formal discharge reports from hospital serve as a post factum formalization and authorization of information collected by municipal nurses in an ad hoc fashion and via oral communication.  Typically, formal information routines are out of phase with the information needed by municipal care professionals. Conclusions: Hospital information provided at discharge is neither sufficient nor timely with respect to the information needs of nurses in municipal care. Organizational efforts and the use of information technology might ease some obstacles, but several problems will remain because of differences in professional orientation and the contexts of care delivery.